Brief communication: "Determination of urban growth in catchment areas in Cyprus using multi-temporal remotely sensed data: Risk assessment study" - Hadjimitsis, Diofantos G. (My University, 2010)
The aim of this study is to quantify the actual urbanization activity near the catchment area in the urban area of interest located in the vicinity of the Agriokalamin River area of Kissonerga Village in Paphos District. Remotely sensed data such as aerial photos, Landsat-5/7 TM/ETM+ and Quickbird image data have been used to track the urbanization activity from 1963 to 2008. In-situ GPS measurements have been used to locate in-situ the boundaries of the catchment area. The results clearly illustrate that tremendous urban development has taken place ranging from 0.9 to 33% from 1963 to 2008, respectively. A flood risk assessment and hydraulic analysis were also performed. © Author(s) 2010.
Keywords: Tunnels; Excavation; Land cover